Makna Leksikal dan Kultural Pada Pantang Larang: Studi Etnolinguistik Terhadap Kepercayaan Masyarakat Banjar Kecamatan Bram Itam, Kabupaten Tanjung Jabung Barat - Yuliana, Yessa; Putra, Yoga Mestika; Izar, Julisah (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
The object of this research is the lexical and cultural meaning of the taboos of the Banjar community in Bram Itam District. The method used is a descriptive qualitative approach through interviews and literature analysis, as well as analysis of Charles Carpenter Fries' theory of meaning. The data analysis process includes transcription of taboos, analysis of lexical and Yogyakarta: CV Bintang Semesta Mediacultural meanings, and categorization of taboos. The research findings show 40 taboo expressions classified into 10 categories, with a total of 180 lexical meanings and 44 cultural meanings. The details of the findings include: 32 lexical items and 11 cultural meanings for unmarried girls; 39 lexical items and 7 cultural meanings for pregnant women; 30 lexical items and 4 cultural meanings are general, and other variations. Lexical meanings are obtained from the Banjar-Indonesian dictionary and informants, while cultural meanings are taken from relevant research. Abstrak Objek penelitian ini adalah makna leksikal dan kultural dari pantangan masyarakat Banjar di Kecamatan Bram Itam. Metode yang digunakan adalah pendekatan kualitatif deskriptif melalui wawancara dan analisis kepustakaan, serta analisis teori makna Charles Carpenter Fries. Proses analisis data mencakup transkripsi ujaran pantang-larang, analisis makna leksikal dan kultural, serta pengkategorian pantang-larang. Temuan penelitian menunjukkan 40 ungkapan pantangan yang diklasifikasikan dalam 10 kategori, dengan total 180 makna leksikal dan 44 makna kultural. Rincian temuan mencakup: 32 item leksikal dan 11 makna kultural untuk gadis yang belum menikah; 39 item leksikal dan 7 makna kultural bagi wanita hamil; 30 item leksikal dan 4 makna kultural bersifat umum, serta variasi lainnya. Makna leksikal diperoleh dari kamus Banjar-Indonesia dan informan, sedangkan makna kultural diambil dari penelitian relevan.